Semiconductor nanoparticles and their manufacturing method
By heat-treating silver salt, sulfur and salts containing tin or gallium in an organic solvent and controlling the addition rate of sulfur, the problem of difficult to manufacture semiconductor nanoparticles with narrow particle size distribution in the prior art is solved, and efficient photoluminescence characteristics are achieved.
Patent Information
- Application Number
- JP2020571311
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-26
- Filing Date
- 2020-02-07
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2040-02-07
AI Technical Summary
It is difficult to manufacture semiconductor nanoparticles with narrow particle size distributions, especially in semiconductor quantum dots with core shell structures.
Using a method, semiconductor nanoparticles with narrow particle size distribution are produced by heat treatment of silver salt, sulfur and at least one tin or gallium-containing salt in an organic solvent and controlling the addition rate of sulfur.
The production of semiconductor nanoparticles with narrow particle size distribution is achieved, especially in the core shell structure, and the stability and efficiency of photoluminescent characteristics are improved.
Smart Images

Figure 0007656289000003 
Figure 0007656289000004 
Figure 0007656289000005
Abstract
Description
[Technical field]
[0001] The present invention relates to semiconductor nanoparticles and a method for producing the same. [Background technology]
[0002] It is known that when semiconductor particles have a particle size of, for example, 10 nm or less, the quantum size effect appears, and such nanoparticles are called quantum dots (also called semiconductor quantum dots). The quantum size effect refers to the phenomenon in which the valence band and conduction band, which are considered continuous in bulk particles, become discrete when the particle size is nanosized, and the band gap energy changes depending on the particle size.
[0003] Since quantum dots can absorb light and convert the wavelength of light into light corresponding to the band gap energy, white light emitting devices utilizing the emission of quantum dots have been proposed (see, for example, JP 2012-212862 A and JP 2010-177656 A). Specifically, it has been proposed to absorb a part of the light emitted from a light emitting diode (LED) chip into quantum dots to obtain white light as a mixture of the emission from the quantum dots and the emission from the LED chip. These patent documents propose the use of binary quantum dots of groups 12-16 such as CdSe and CdTe, and groups 14-16 such as PbS and PbSe. In addition, in consideration of the toxicity of compounds containing Cd and Pb, wavelength conversion films using core-shell structured semiconductor quantum dots that do not contain these elements have been proposed (see, for example, WO 2014 / 129067 A). Summary of the Invention [Problem to be solved by the invention]
[0004] In view of luminescence characteristics, semiconductor nanoparticles having a narrow particle size distribution are required as cores constituting core-shell quantum dots. One aspect of the present disclosure aims to provide a method for producing semiconductor nanoparticles capable of producing semiconductor nanoparticles having a narrow particle size distribution. [Means for solving the problem]
[0005] A first aspect is a method for producing semiconductor nanoparticles, comprising: preparing a mixture containing a silver (Ag) salt, a salt containing at least one of indium (In) and gallium (Ga), and an organic solvent; heating the mixture to a temperature in the range of 120°C or higher and 300°C or lower; and adding a sulfur (S) source to the heated mixture so that the rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture is 10 / min or lower.
[0006] A second aspect is a method for producing semiconductor nanoparticles, comprising: preparing a mixture containing a silver (Ag) salt, a copper (Cu) salt, a salt containing at least one of indium (In) and gallium (Ga), and an organic solvent; heating the mixture to a temperature in the range of 120°C or higher and 300°C or lower; and adding a sulfur (S) source to the heated mixture so that the rate of increase in the ratio of the number of S atoms to the sum of the number of Ag atoms and the number of Cu atoms in the mixture is 10 / min or lower.
[0007] A third aspect is a semiconductor nanoparticle that contains silver (Ag), copper (Cu), at least one of indium (In) and gallium (Ga), and sulfur (S), in which the ratio of the number of Cu atoms to the total number of Ag and Cu atoms is 0.001 or more and 0.9 or less, and that, when irradiated with light having a wavelength within the range of 350 nm or more and less than 500 nm, emits light having a longer wavelength than the irradiated light.
[0008] A fourth aspect is a core-shell type semiconductor nanoparticle comprising a core containing semiconductor nanoparticles that contain silver (Ag) and copper (Cu), at least one of indium (In) and gallium (Ga), and sulfur (S), in which the ratio of the number of Cu atoms to the total number of Ag and Cu atoms is 0.001 or more and 0.9 or less, and a shell that is disposed on the surface of the core and contains a semiconductor material substantially consisting of a Group 13 element and a Group 16 element, and that emits light having an emission peak wavelength in the range of 500 nm or more and 820 nm or less and a half-width in the emission spectrum of 250 meV or less when irradiated with light having a wavelength in the range of 350 nm or more and less than 500 nm.
[0009] A fifth aspect is a light-emitting device including a light conversion member containing the semiconductor nanoparticles and a semiconductor light-emitting element. Effect of the Invention
[0010] According to one aspect of the present disclosure, it is possible to provide a method for producing semiconductor nanoparticles that is capable of producing semiconductor nanoparticles having a narrow particle size distribution. [Brief description of the drawings]
[0011] [Figure 1] 2 is an example of an X-ray diffraction (XRD) pattern of the semiconductor nanoparticles according to Example 1. [Diagram 2] 2 is an example of an absorption spectrum of the core-shell type semiconductor nanoparticles according to Example 1. [Diagram 3] 2 is an example of an emission spectrum of the semiconductor nanoparticles according to Example 1. [Figure 4] 1 is an example of an XRD pattern of semiconductor nanoparticles according to Comparative Example 1. [Diagram 5] 1 is an example of an absorption spectrum of semiconductor nanoparticles according to Comparative Example 1. [Figure 6] 1 is an example of an emission spectrum of semiconductor nanoparticles according to Comparative Example 1. [Figure 7] 1 shows examples of absorption spectra of semiconductor nanoparticles according to Examples 2 and 3 and Comparative Example 2. [Figure 8]1 shows examples of emission spectra of semiconductor nanoparticles according to Examples 2 and 3 and Comparative Example 2. [Figure 9] 1 shows examples of absorption spectra of core-shell type semiconductor nanoparticles according to Examples 2 and 3 and Comparative Example 2. [Figure 10] 1 shows examples of emission spectra of core-shell type semiconductor nanoparticles according to Examples 2 and 3 and Comparative Example 2. [Figure 11] 1 shows an example of X-ray diffraction (XRD) patterns of the semiconductor nanoparticles according to Examples 4, 5 and 6. [Figure 12] 1 is an example of an absorption spectrum of semiconductor nanoparticles according to Example 4. [Figure 13] 1 is an example of an emission spectrum of the semiconductor nanoparticles according to Example 4. [Figure 14] 13 is an example of an absorption spectrum of the semiconductor nanoparticles of Example 5. [Figure 15] 13 is an example of an emission spectrum of the semiconductor nanoparticles according to Example 5. [Figure 16] 13 is an example of an absorption spectrum of the semiconductor nanoparticles of Example 6. [Figure 17] 13 is an example of an emission spectrum of the semiconductor nanoparticles according to Example 6. [Figure 18] 13 is an example of an absorption spectrum of the semiconductor nanoparticles of Example 7. [Figure 19] 13 is an example of an emission spectrum of the semiconductor nanoparticles of Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. Furthermore, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. Hereinafter, the embodiments will be described in detail. However, the embodiments shown below are examples of semiconductor nanoparticles and their manufacturing methods for embodying the technical idea of the present invention, and the present invention is not limited to the semiconductor nanoparticles and their manufacturing methods shown below.
[0013] Method for producing semiconductor nanoparticles A first aspect of the method for producing semiconductor nanoparticles includes a preparation step of preparing a mixture containing an Ag salt, a salt containing at least one of In and Ga, and an organic solvent, a heating step of heating the mixture to a temperature in the range of 120°C or more and 300°C or less, and an addition step of adding a source of S to the heated mixture so that the rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture is 10 / min or less.
[0014] A mixture containing elements other than S among those constituting the semiconductor nanoparticles and an organic solvent is prepared in advance, and while the mixture is heated, a stoichiometric amount of a source of S is gradually added so that the rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture is 10 / min or less, thereby producing semiconductor nanoparticles with a narrow particle size distribution. This can be considered to be because, for example, the concentration of S in the reaction solution that produces the semiconductor nanoparticles is kept sufficiently low, thereby controlling the particle growth of the semiconductor nanoparticles, particularly the intermediate product silver sulfide nanoparticles.
[0015] A second aspect of the method for producing semiconductor nanoparticles includes a preparation step of preparing a mixture containing an Ag salt, a Cu salt, a salt containing at least one of In and Ga, and an organic solvent, a heating step of heating the mixture to a temperature in the range of 120°C or more and 300°C or less, and an addition step of adding a source of S to the heated mixture so that the rate of increase in the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 10 / min or less.
[0016] A mixture containing elements other than S among those constituting the semiconductor nanoparticles and an organic solvent is prepared in advance, and while the mixture is heated, a stoichiometric amount of a source of S is gradually added so that the rate of increase in the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 10 / min or less, thereby making it possible to produce semiconductor nanoparticles with a narrow particle size distribution. This can be considered to be because, for example, the concentration of S in the reaction solution that produces the semiconductor nanoparticles is kept sufficiently low, thereby controlling the particle growth of the semiconductor nanoparticles, particularly the intermediate product, sulfide nanoparticles that contain silver and may contain copper.
[0017] Preparation process In the preparation step of the first embodiment, a mixture (hereinafter also referred to as a first mixture) containing an Ag salt, a salt containing at least one of In and Ga, and an organic solvent is prepared. The mixture can be prepared by mixing an Ag salt and a salt containing at least one of In and Ga with an organic solvent. The mixture may also be prepared by mixing an Ag salt or a salt containing at least one of In and Ga with an organic solvent, and then mixing the remaining components. The resulting mixture may be in a solution state without undissolved matter at an elevated temperature. The mixing atmosphere may be an inert gas atmosphere, such as an argon atmosphere, a nitrogen atmosphere, or the like. By using an inert gas atmosphere, the by-production of oxides can be reduced or prevented.
[0018] In the preparation step of the second embodiment, a mixture (hereinafter also referred to as a first mixture) containing an Ag salt, a Cu salt, a salt containing at least one of In and Ga, and an organic solvent is prepared. The mixture can be prepared by mixing an Ag salt, a Cu salt, and a salt containing at least one of In and Ga with an organic solvent. The mixture may also be prepared by mixing an Ag salt, a Cu salt, or a salt containing at least one of In and Ga with an organic solvent, and then mixing the remaining components. The resulting mixture may be in a solution state without undissolved matter at an elevated temperature. The mixing atmosphere may be an inert gas atmosphere, such as an argon atmosphere, a nitrogen atmosphere, or the like. By using an inert gas atmosphere, the by-production of oxides can be reduced or prevented.
[0019] Examples of the Ag salt, Cu salt, and salt containing at least one of In and Ga used in the production method include organic acid salts and inorganic acid salts. Specific examples of inorganic acid salts include nitrates, sulfates, hydrochlorides, sulfonates, and carbonates. Examples of organic acid salts include acetates and acetylacetonates. Among these, organic acid salts are preferred because of their high solubility in organic solutions.
[0020] Examples of organic solvents include amines having a hydrocarbon group with 4 to 20 carbon atoms, particularly alkylamines or alkenylamines having 4 to 20 carbon atoms; thiols having a hydrocarbon group with 4 to 20 carbon atoms, particularly alkylthiols or alkenylthiols having 4 to 20 carbon atoms; phosphines having a hydrocarbon group with 4 to 20 carbon atoms, particularly alkylphosphines or alkenylphosphines having 4 to 20 carbon atoms. These organic solvents can ultimately be used to modify the surface of the semiconductor nanoparticles obtained. Two or more of these organic solvents may be used in combination, and in particular, a mixed solvent may be used that combines at least one selected from thiols having a hydrocarbon group with 4 to 20 carbon atoms and at least one selected from amines having a hydrocarbon group with 4 to 20 carbon atoms. These organic solvents may also be used in combination with other organic solvents. In addition, the organic solvent may be solid at room temperature as long as it dissolves at 120°C or higher.
[0021] The ratio of the number of Ag atoms to the total number of In and Ga atoms contained in the mixture in the first embodiment (Ag / (In+Ga)) may be, for example, 0.1 to 2, and preferably 0.5 to 1.2. The concentration of Ag in the mixture may be, for example, 1 mmol / L to 500 mmol / L, and preferably 10 mmol / L to 50 mmol / L.
[0022] In the second embodiment, the ratio of the total number of Ag and Cu atoms to the total number of In and Ga atoms ((Ag+Cu) / (In+Ga)) contained in the mixture may be, for example, 0.1 to 2, and preferably 0.5 to 1.2. The ratio of the number of Cu atoms to the total number of Ag and Cu atoms contained in the mixture (Cu / (Ag+Cu)) may be, for example, 0.001 to 0.9, and preferably 0.005 to 0.5. The total concentration of Ag and Cu in the mixture may be, for example, 1 mmol / L to 500 mmol / L, and preferably 10 mmol / L to 50 mmol / L.
[0023] Heating process In the temperature-raising step, the prepared mixture may be heated to a temperature in the range of 120° C. or more and 300° C. or less. The temperature reached by the temperature rise is preferably 125° C. or more, more preferably 130° C. or more, and even more preferably 135° C. or more. The temperature reached by the temperature rise is preferably 175° C. or less, more preferably 160° C. or less, and even more preferably 150° C. or less. The temperature rise rate may be, for example, 1° C. / min. or more and 50° C. / min. or less, and is preferably 10° C. / min. or more and 50° C. / min. or less.
[0024] The atmosphere during the temperature rise of the mixture may be an inert gas atmosphere, and is preferably, for example, an argon atmosphere, a nitrogen atmosphere, etc. By using an inert gas atmosphere, the by-production of oxides can be reduced or prevented.
[0025] Addition process In the addition step in the first embodiment, the S source is gradually added to the mixture heated to a predetermined temperature while maintaining the predetermined temperature so that the rate of increase of the ratio of the number of S atoms to the number of Ag atoms in the mixture is 10 / min or less. The rate of increase of the ratio of the number of S atoms to the number of Ag atoms in the mixture (S / Ag ratio) is calculated, for example, by subtracting the S / Ag ratio at a certain time from the S / Ag ratio after that unit time, and dividing the result by the value obtained by converting the unit time into minutes. The unit time is, for example, arbitrarily selected between 1 second and 1 minute. From the viewpoint of particle growth control of silver sulfide nanoparticles, the rate of increase of the ratio of the number of S atoms to the number of Ag atoms in the mixture is preferably 0.0001 / min or more and 2 / min or less, more preferably 0.0001 / min or more and 1 / min or less, even more preferably 0.001 / min or more and 0.2 / min or less, and particularly preferably 0.001 / min or more and 0.1 / min or less. Also, it is preferably 0.0002 / min or more and 2 / min or less, more preferably 0.002 / min or more and 0.2 / min or less, even more preferably 0.0025 / min or more and 0.19 / min or less, and particularly preferably 0.04 / min or more and 0.12 / min or less. The increase rate of the S / Ag ratio may be, for example, 0.0001 / min or more, preferably 0.0002 / min or more, 0.001 / min or more, 0.002 / min or more, 0.0025 / min or more, 0.005 / min or more, 0.01 / min or more, or 0.04 / min or more. The increase rate of the S / Ag ratio may be, for example, 5 / min or less, preferably 2 / min or less, 1 / min or less, 0.5 / min or less, 0.3 / min or less, 0.25 / min or less, 0.2 / min or less, or 0.19 / min or less.
[0026] The total amount of the S source added in the first embodiment may be an amount such that the ratio of the number of S atoms to the number of Ag atoms in the mixture is 0.1 to 5, and preferably 1 to 2.5. The time required for adding the S source may be, for example, 1 minute or more, preferably 5 minutes or more, more preferably 15 minutes or more, and even more preferably 20 minutes or more. The time required may be, for example, 120 minutes or less, preferably 60 minutes or less, and more preferably 40 minutes or less.
[0027] When the total amount of the S source added is an amount such that the ratio of the number of S atoms to the number of Ag atoms in the mixture is 0.1 or more and 2.5 or less, the rate of increase in the S / Ag ratio may be, for example, 0.0001 / min or more and 1 / min or less, preferably 0.001 / min or more and 0.2 / min or less, more preferably 0.002 / min or more and 0.2 / min or less, even more preferably 0.0025 / min or more and 0.19 / min or less, and particularly preferably 0.04 / min or more and 0.12 / min or less. Furthermore, when the total amount of the S source added is an amount such that the ratio of the number of S atoms to the number of Ag atoms in the mixture is more than 2.5 and not more than 5.0, the rate of increase in the S / Ag ratio may be, for example, 0.0002 / min or more and 2 / min or less, preferably 0.002 / min or more and 0.2 / min or less, more preferably 0.0025 / min or more and 0.19 / min or less, and even more preferably 0.04 / min or more and 0.12 / min or less.
[0028] In the addition step in the second embodiment, the S source is gradually added to the mixture heated to a predetermined temperature while maintaining the predetermined temperature so that the rate of increase of the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 10 / min or less. The rate of increase of the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture (S / (Ag+Cu) ratio) is calculated, for example, by subtracting the S / (Ag+Cu) ratio at a certain time from the S / (Ag+Cu) ratio after that unit time, and dividing the result by the value obtained by converting the unit time into minutes. The unit time is, for example, selected arbitrarily between 1 second and 1 minute. The rate of increase in the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is preferably 0.0001 / min to 2 / min from the viewpoint of particle growth control of sulfide nanoparticles that contain silver and may contain copper, more preferably 0.0001 / min to 1 / min, even more preferably 0.001 / min to 0.2 / min, and particularly preferably 0.001 / min to 0.1 / min. Also, it is preferably 0.0002 / min to 2 / min, more preferably 0.002 / min to 0.2 / min, even more preferably 0.0025 / min to 0.19 / min, and particularly preferably 0.04 / min to 0.12. The rate of increase of the S / (Ag+Cu) ratio may be, for example, 0.0001 / min or more, preferably 0.0002 / min or more, 0.001 / min or more, 0.002 / min or more, 0.0025 / min or more, 0.005 / min or more, 0.01 / min or more, or 0.04 / min or more. The rate of increase of the S / Ag ratio may be, for example, 5 / min or less, preferably 2 / min or less, 1 / min or less, 0.5 / min or less, 0.3 / min or less, 0.25 / min or less, 0.2 / min or less, or 0.19 / min or less.
[0029] The total amount of the S source added in the second embodiment may be an amount such that the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 0.1 to 5, and preferably 1 to 2.5. The time required for adding the S source may be, for example, 1 minute or more, preferably 5 minutes or more, more preferably 15 minutes or more, and even more preferably 20 minutes or more. The time required may be, for example, 120 minutes or less, preferably 60 minutes or less, and more preferably 40 minutes or less.
[0030] When the total amount of the S source added is an amount such that the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 0.1 or more and 2.5 or less, the rate of increase in the S / (Ag+Cu) ratio may be, for example, 0.0001 / min or more and 1 / min or less, preferably 0.001 / min or more and 0.2 / min or less, more preferably 0.002 / min or more and 0.2 / min or less, even more preferably 0.0025 / min or more and 0.19 / min or less, and particularly preferably 0.04 / min or more and 0.12 / min or less. Furthermore, when the total amount of the S source added is an amount such that the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is more than 2.5 and not more than 5, the rate of increase in the S / (Ag+Cu) ratio may be, for example, 0.0002 / min or more and 2 / min or less, preferably 0.002 / min or more and 0.2 / min or less, more preferably 0.0025 / min or more and 0.19 / min or less, and even more preferably 0.04 / min or more and 0.12 / min or less.
[0031] The S source may be added so that the amount added per unit time is approximately the same over the required time. That is, the total amount of the S source added may be divided by the required time divided by the unit time to obtain a unit amount added per unit time. The unit time may be, for example, 1 second, 5 seconds, 10 seconds, 30 seconds, or 1 minute. The S source may be added continuously or stepwise. The S source may be added to the mixture, for example, under an inert gas atmosphere.
[0032] Examples of the source of S include sulfur or a sulfur-containing compound. Specific examples of the sulfur-containing compound include β-dithiones such as 2,4-pentanedithione; dithiols such as 1,2-bis(trifluoromethyl)ethylene-1,2-dithiol; dialkyldithiocarbamate such as diethyldithiocarbamate; and alkylthioureas such as thiourea, 1,3-dialkylthiourea having an alkyl group with 1 to 18 carbon atoms, 1,1-dialkylthiourea, alkylthiourea, 1,1,3-trialkylthiourea, and 1,1,3,3-tetraalkylthiourea. As the source of S, a sulfur-containing compound that can be dissolved in an organic solvent is preferred, and from the viewpoint of solubility and reactivity, alkylthiourea is more preferred, and 1,3-dialkylthiourea is even more preferred. As the alkyl group of the alkylthiourea, the number of carbon atoms is preferably 1 to 12, more preferably 1 to 8, more preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 3. When the alkylthiourea has multiple alkyl groups, they may be the same or different.
[0033] The S source may be added to the mixture as a solution of sulfur or a sulfur-containing compound dissolved in an organic solvent. When the S source is a solution of a sulfur-containing compound, the amount of the S source added per unit time in the addition step can be easily controlled, and semiconductor nanoparticles with a narrower particle size distribution can be efficiently produced.
[0034] Examples of organic solvents for dissolving the sulfur-containing compound that serves as the S source include the same organic solvents as those contained in the mixture described above. For example, an amine having a hydrocarbon group having 4 to 20 carbon atoms can be used.
[0035] When the S source is a solution of a sulfur-containing compound, the concentration of the sulfur-containing compound may be, for example, 1 mmol / L or more and 500 mmol / L or less, and preferably 10 mmol / L or more and 50 mmol / L or less.
[0036] Heat Treatment Process The method for producing semiconductor nanoparticles may further include a heat treatment step of heat treating the mixture after the addition of the S source at a temperature in the range of 120°C to 300°C. The temperature of the heat treatment may be the same as or different from the temperature to which the mixture is heated. From the viewpoint of quantum yield, the temperature of the heat treatment may be, for example, 120°C to 300°C, preferably 125°C to 175°C, more preferably 130°C to 160°C, and even more preferably 135°C to 150°C.
[0037] The time of the heat treatment may be, for example, 3 seconds or more, preferably 5 minutes or more, 10 minutes or more, or 20 minutes or more, from the viewpoint of the quantum efficiency of the semiconductor nanoparticles. The upper limit of the heat treatment time is not particularly limited, but may be, for example, 60 minutes or less. The time of the heat treatment is set to the time when a predetermined temperature is reached (for example, the time when 140°C is reached in the case of 140°C), and the time when the operation for lowering the temperature is performed is set to the time when the heat treatment is ended.
[0038] The heat treatment may be performed in an inert gas atmosphere, preferably an argon atmosphere or a nitrogen atmosphere, which can reduce or prevent the generation of oxides as by-products and the oxidation of the surfaces of the resulting semiconductor nanoparticles.
[0039] The method for producing semiconductor nanoparticles may include a cooling step of lowering the temperature of the solution containing the semiconductor nanoparticles following the synthesis step described above. The cooling step is started when an operation for lowering the temperature is performed and is ended when the solution is cooled to 50° C. or less.
[0040] The cooling step may include a period during which the temperature is lowered at a rate of 50° C. / min or more in order to suppress the generation of silver sulfide from unreacted Ag salts or copper sulfide from unreacted Cu salts. For example, the rate may be 50° C. / min or more at the start of the temperature lowering operation after the temperature lowering operation is performed.
[0041] The cooling step is preferably performed in an inert gas atmosphere, such as an argon atmosphere or a nitrogen atmosphere. By using an inert gas atmosphere, the production of oxides as by-products can be reduced or prevented, and oxidation of the surfaces of the obtained semiconductor nanoparticles can be reduced or prevented.
[0042] The method for producing semiconductor nanoparticles may further include a separation step of separating the semiconductor nanoparticles from the solution, and may further include a purification step as necessary. In the separation step, for example, the solution containing the semiconductor nanoparticles may be centrifuged to remove the supernatant containing the nanoparticles. In the purification step, for example, an appropriate organic solvent such as alcohol may be added to the supernatant obtained in the separation step and centrifuged to remove the semiconductor nanoparticles as a precipitate. The semiconductor nanoparticles can also be removed by volatilizing the organic solvent from the supernatant. The removed precipitate may be dried, for example, by vacuum degassing, natural drying, or a combination of vacuum degassing and natural drying. Natural drying may be performed, for example, by leaving the mixture in the air at room temperature and normal pressure, and in that case, the mixture may be left for 20 hours or more, for example, about 30 hours. The removed precipitate may also be dispersed in an appropriate organic solvent.
[0043] In the method for producing semiconductor nanoparticles, a purification step involving addition of an organic solvent such as alcohol and centrifugation may be carried out multiple times as necessary. As the alcohol used for purification, a lower alcohol having 1 to 4 carbon atoms such as methanol, ethanol, or n-propyl alcohol may be used. When dispersing the precipitate in an organic solvent, as the organic solvent, a halogen-based solvent such as chloroform, dichloromethane, dichloroethane, trichloroethane, or tetrachloroethane, or a hydrocarbon-based solvent such as toluene, cyclohexane, hexane, pentane, or octane may be used. From the viewpoint of quantum yield, the organic solvent in which the precipitate is dispersed may be a halogen-based solvent.
[0044] The semiconductor nanoparticles obtained by the manufacturing method of the first embodiment described above contain Ag, at least one of In and Ga, and S. Semiconductor nanoparticles containing Ag, In, and S and having a tetragonal, hexagonal, or orthorhombic crystal structure are generally introduced in literature as being represented by the composition formula AgInS2. On the other hand, in reality, they are not of the stoichiometric composition represented by the above general formula, and in particular, the ratio of the number of Ag atoms to the number of In and Ga atoms (Ag / In+Ga) may be smaller than 1, or conversely, may be larger than 1. In addition, the sum of the number of Ag atoms and the total number of In and Ga atoms may not be the same as the number of S atoms. Therefore, in this specification, for a semiconductor containing a specific element, in a situation where it does not matter whether it is a stoichiometric composition or not, the semiconductor composition is expressed by a formula in which the constituent elements are connected with "-", such as Ag-In-S. Therefore, the semiconductor nanoparticles can be considered to be, for example, Ag-In-S and Ag-In-Ga-S or Ag-Ga-S in which some or all of the In, a group 13 element, is replaced by Ga, also a group 13 element.
[0045] The semiconductor nanoparticles of the third embodiment obtained by the manufacturing method of the second embodiment contain Ag, Cu, at least one of In and Ga, and S. Semiconductor nanoparticles containing Ag, In, and S and having a tetragonal, hexagonal, or orthorhombic crystal structure are generally introduced in literature as being represented by the composition formula AgInS2. On the other hand, in reality, they are not of the stoichiometric composition represented by the above general formula, and in particular, the ratio of the number of Ag atoms to the number of In and Ga atoms ((Ag+Cu) / (In+Ga)) may be smaller than 1, or conversely, may be larger than 1. In addition, the sum of the total number of Ag and Cu atoms and the total number of In and Ga atoms may not be the same as the number of S atoms. Therefore, in this specification, when a semiconductor containing a specific element is in a situation where it does not matter whether it is a stoichiometric composition, the semiconductor composition may be expressed by a formula in which the constituent elements are connected with "-", such as Ag-Cu-In-S. Therefore, the semiconductor nanoparticles can be considered to be, for example, Ag-Cu-In-S, Ag-Cu-In-Ga-S in which some or all of the In, a group 13 element, is replaced with Ga, also a group 13 element, or Ag-Cu-Ga-S.
[0046] The semiconductor nanoparticles of the third embodiment contain Ag, Cu, at least one of In and Ga, and S, and the ratio of the number of Cu atoms to the total number of Ag and Cu atoms may be 0.001 or more and 0.9 or less, and emit light having a longer wavelength than the irradiated light when irradiated with light having a wavelength in the range of 350 nm to less than 500 nm. The ratio of the number of Cu atoms to the total number of Ag and Cu atoms may be 0.001 or more and 0.9 or less, and may be 0.005 or more and 0.5 or less. The light having a longer wavelength than the irradiated light may be light having an emission peak wavelength in a wavelength range longer than the irradiated light.
[0047] The semiconductor nanoparticles may have a ratio of the total number of In and Ga atoms to the total number of Ag and Cu atoms of 0.5 to 10, or 0.8 to 5, or 0.9 to 2. The semiconductor nanoparticles may have a ratio of the number of S atoms to the total number of Ag and Cu atoms of 1 to 10, or 1.5 to 8, or 2 to 3.
[0048] In addition, among the semiconductor nanoparticles containing the above elements, those having a hexagonal crystal structure are wurtzite type, and those having a tetragonal crystal structure are chalcopyrite type. The crystal structure is identified, for example, by measuring an XRD pattern obtained by X-ray diffraction (XRD) analysis. Specifically, the XRD pattern obtained from the semiconductor nanoparticles is compared with a known XRD pattern of a semiconductor nanoparticle represented by a composition of AgInS2, or an XRD pattern obtained by performing a simulation from crystal structure parameters. If any of the known patterns and the simulation patterns match the pattern of the semiconductor nanoparticles, the crystal structure of the semiconductor nanoparticles can be said to be the crystal structure of the matching known or simulation pattern.
[0049] In the aggregate of semiconductor nanoparticles, semiconductor nanoparticles of different crystal structures may be mixed. In that case, peaks derived from a plurality of crystal structures are observed in the XRD pattern. In the core-shell type semiconductor nanoparticles of the first embodiment, since the core-shell type semiconductor nanoparticles are substantially composed of tetragonal crystals, peaks corresponding to tetragonal crystals are observed, and peaks derived from other crystal structures are not substantially observed.
[0050] Although Ag may be partially substituted with Au or the like, it is preferable that the material is substantially composed of Ag or Ag and Cu. Here, "substantially" indicates that the ratio of elements other than Ag and Cu to Ag and Cu is, for example, 10 mol % or less, preferably 5 mol % or less, and more preferably 1 mol % or less.
[0051] At least one of In and Ga may be partially substituted with at least one of Al and Tl, but it is preferable that the material is substantially composed of at least one of In and Ga. Here, "substantially" indicates that the ratio of elements other than In and Ga to the total of In and Ga is, for example, 10 mol % or less, preferably 5 mol % or less, and more preferably 1 mol % or less.
[0052] S may be partially substituted with at least one of Se and Te, but is preferably substantially composed of S. Here, "substantially" indicates that the ratio of elements other than S to S is, for example, 10 mol % or less, preferably 5 mol % or less, and more preferably 1 mol % or less.
[0053] The semiconductor nanoparticles obtained by the manufacturing method of the first embodiment may be substantially composed of Ag, In, Ga, S, and the elements partially substituted therewith. Here, the term "substantially" is used in consideration of the fact that elements other than Ag, In, Ga, S, and the elements partially substituted therewith are inevitably included due to the inclusion of impurities, etc.
[0054] The semiconductor nanoparticles obtained by the production method of the second embodiment may be substantially composed of Ag, Cu, In, Ga, S, and the elements partially substituted therewith. Here, the term "substantially" is used in consideration of the fact that elements other than Ag, Cu, In, Ga, S, and the elements partially substituted therewith are inevitably included due to the inclusion of impurities, etc.
[0055] The semiconductor nanoparticles may have an average particle size of, for example, 10 nm or less, particularly 8 nm or less. The average particle size of the semiconductor nanoparticles may be in the range of 1.5 nm to 10 nm, particularly 1.7 nm to 7.5 nm. When the average particle size of the semiconductor nanoparticles is equal to or less than the upper limit, the quantum size effect is easily obtained.
[0056] The average particle size of the semiconductor nanoparticles may be determined, for example, from a TEM image taken using a transmission electron microscope (TEM). Specifically, the particle size of the semiconductor nanoparticles refers to the longest line segment that connects any two points on the periphery of the particle observed in the TEM image and exists inside the particle.
[0057] The average particle size of semiconductor nanoparticles is determined by measuring the particle size of all measurable particles observed in a TEM image at a magnification of 50,000 times or more and 150,000 times or less, and calculating the arithmetic average of the particle sizes. Here, a "measurable" particle is one whose entirety can be observed in a TEM image. Therefore, a particle that is "cut off" because a part of it is not included in the imaging range in a TEM image is not measurable. If the number of measurable particles contained in one TEM image is 100 or more, the average particle size is determined using that TEM image. On the other hand, if the number of measurable particles contained in one TEM image is less than 100, the imaging location is changed, another TEM image is obtained, and the particle sizes of 100 or more measurable particles contained in two or more TEM images are measured to determine the average particle size.
[0058] The semiconductor nanoparticles obtained by the above-mentioned production method may be used as a core to form a shell on the surface of the core to constitute core-shell type semiconductor nanoparticles. By forming the core-shell type semiconductor nanoparticles, for example, better band edge emission is possible.
[0059] The shell is composed of a semiconductor having a larger band gap energy than the semiconductor constituting the core, and includes a group 13 element and a group 16 element. Examples of group 13 elements include B, Al, Ga, In, and Tl, and examples of group 16 elements include O, S, Se, Te, and Po. The semiconductor constituting the shell may include only one type of group 13 element or two or more types of group 16 element, and may include only one type of group 16 element or two or more types of group 16 element.
[0060] The shell may be composed of a semiconductor substantially consisting of Group 13 elements and Group 16 elements. Here, "substantially" means that, when the total number of atoms of all elements contained in the shell is taken as 100%, the proportion of the number of atoms of elements other than Group 13 elements and Group 16 elements is, for example, 10% or less, preferably 5% or less, and more preferably 1% or less.
[0061] The shell may be configured by selecting its composition, etc., depending on the band gap energy of the semiconductor constituting the core. Alternatively, when the composition, etc., of the shell is determined in advance, the core may be designed so that the band gap energy of the semiconductor constituting the core is smaller than that of the shell. In general, a semiconductor made of Ag-In-S has a band gap energy of 1.8 eV or more and 1.9 eV or less.
[0062] Specifically, the semiconductor constituting the shell may have a band gap energy of, for example, 2.0 eV to 5.0 eV, particularly 2.5 eV to 5.0 eV. The band gap energy of the shell may be, for example, about 0.1 eV to 3.0 eV, particularly about 0.3 eV to 3.0 eV, more particularly about 0.5 eV to 1.0 eV, higher than the band gap energy of the core. If the difference between the band gap energy of the semiconductor constituting the shell and the band gap energy of the semiconductor constituting the core is equal to or greater than the lower limit, the proportion of emission other than band edge emission in the emission from the core tends to be small, and the proportion of band edge emission tends to be large.
[0063] Furthermore, the band gap energy of the semiconductors constituting the core and shell is preferably selected so as to provide a type-I band alignment in which the band gap energy of the shell sandwiches the band gap energy of the core at the heterojunction of the core and the shell. By forming the type-I band alignment, it is possible to obtain better band edge emission from the core. In the type-I alignment, it is preferable that a barrier of at least 0.1 eV is formed between the band gap of the core and the band gap of the shell, and for example, a barrier of 0.2 eV or more or 0.3 eV or more may be formed. The upper limit of the barrier is, for example, 1.8 eV or less, particularly 1.1 eV or less. If the barrier is equal to or greater than the lower limit, the proportion of emission other than band edge emission in the emission from the core tends to be small, and the proportion of band edge emission tends to be large.
[0064] The semiconductor constituting the shell may contain In or Ga as a Group 13 element. The shell may also contain S as a Group 16 element. Semiconductors containing In or Ga or containing S tend to be semiconductors having a larger band gap energy than the above-mentioned core.
[0065] The shell may be a semiconductor whose crystal system is familiar to that of the core semiconductor, and whose lattice constant is the same or close to that of the core semiconductor. A shell made of a semiconductor whose crystal system is familiar to the core and whose lattice constant is close (here, a shell whose lattice constant multiple is close to that of the core is also considered to be close) may well cover the periphery of the core. For example, the above-mentioned core is generally tetragonal, and examples of crystal systems familiar to it include tetragonal and orthorhombic systems. When Ag-In-S is tetragonal, their lattice constants are 0.5828 nm, 0.5828 nm, and 1.119 nm, respectively, and it is preferable that the shell covering it is tetragonal or cubic, and its lattice constant or its multiple is close to that of Ag-In-S. Alternatively, the shell may be amorphous.
[0066] Whether or not an amorphous shell is formed can be confirmed by observing the core-shell structured semiconductor nanoparticles with HAADF-STEM. When an amorphous shell is formed, specifically, a part having a regular pattern (for example, a striped pattern or a dot pattern, etc.) is observed in the center, and a part not observed as having a regular pattern is observed around it in HAADF-STEM. According to HAADF-STEM, a substance having a regular structure such as a crystalline substance is observed as an image having a regular pattern, and a substance not having a regular structure such as an amorphous substance is not observed as an image having a regular pattern. Therefore, when the shell is amorphous, the shell can be observed as a part that is clearly different from the core (which has a crystal structure such as a tetragonal system as described above) observed as an image having a regular pattern.
[0067] Furthermore, when the shell is made of Ga-S, since Ga is a lighter element than the Ag and In contained in the core, the shell tends to be observed as a darker image than the core in the image obtained by HAADF-STEM.
[0068] Whether or not an amorphous shell is formed can also be confirmed by observing semiconductor nanoparticles with a core-shell structure using a high-resolution transmission electron microscope (HRTEM). In the image obtained with HRTEM, the core portion is observed as a crystal lattice image (an image with a regular pattern), while the shell portion is not observed as a crystal lattice image, and is observed as a portion in which black and white contrast is observed but no regular pattern is visible.
[0069] On the other hand, it is preferable that the shell does not form a solid solution with the core. If the shell forms a solid solution with the core, the two become one, and band edge emission may not be obtained. For example, it has been confirmed that band edge emission cannot be obtained from the core even if the surface of a core made of Ag-In-S is covered with zinc sulfide (Zn-S) of stoichiometric or non-stoichiometric composition. In relation to Ag-In-S, Zn-S satisfies the above conditions regarding band gap energy and provides type-I band alignment. Nevertheless, the reason why band edge emission was not obtained from the specific semiconductor is presumably because the specific semiconductor and ZnS form a solid solution, and the core-shell interface disappears.
[0070] The shell may include, but is not limited to, a combination of In and S, a combination of Ga and S, or a combination of In, Ga and S, as a combination of Group 13 elements and Group 16 elements. The combination of In and S may be in the form of indium sulfide, and the combination of Ga and S may be in the form of gallium sulfide, and the combination of In, Ga and S may be indium gallium sulfide. The indium sulfide constituting the shell does not have to be of stoichiometric composition (In2S3), and in this sense, indium sulfide is referred to herein as having the formula InSx (x is not limited to an integer, but may be any number, for example, 0.8 to 1.5.) Similarly, gallium sulfide does not have to be stoichiometric (Ga2S3), and in this sense, gallium sulfide is referred to herein as having the formula GaS x (x is not limited to an integer, but may be any number, for example, 0.8 to 1.5). Indium gallium sulfide is In 2(1-y) Ga 2y S3 (where y is any number greater than 0 and less than 1), or In a G a1-a S b (where a is any number greater than 0 and less than 1, and b is any number not limited to integers).
[0071] Indium sulfide has a band gap energy of 2.0 eV or more and 2.4 eV or less, and the lattice constant of the cubic crystal system is 1.0775 nm. Gallium sulfide has a band gap energy of about 2.5 eV or more and 2.6 eV or less, and the lattice constant of the tetragonal crystal system is 0.5215 nm. However, the crystal systems described here are all reported values, and the shells of actual core-shell semiconductor nanoparticles do not necessarily meet these reported values.
[0072] Indium sulfide and gallium sulfide are preferably used as semiconductors constituting the shell disposed on the surface of the core. In particular, gallium sulfide is preferably used because it has a larger band gap energy. When gallium sulfide is used, stronger band edge emission can be obtained compared to when indium sulfide is used.
[0073] The particle size of the core-shell type semiconductor nanoparticles may be, for example, an average particle size of 50 nm or less. From the viewpoint of ease of production and quantum yield of band edge emission, the average particle size is preferably in the range of 1 nm to 20 nm, more preferably 1.6 nm to 8 nm, and particularly preferably 2 nm to 7.5 nm. The average particle size of the core-shell type semiconductor nanoparticles is measured in the same manner as the average particle size of the semiconductor nanoparticles described above.
[0074] The thickness of the shell may be, for example, in the range of 0.1 nm to 50 nm, preferably in the range of 0.1 nm to 10 nm, and more preferably in the range of 0.3 nm to 3 nm. When the thickness of the shell is equal to or greater than the lower limit, the effect of the shell covering the core is sufficiently obtained, and band edge emission is easily obtained.
[0075] The shell thickness may be determined by observing the core-shell semiconductor nanoparticles, for example, with HAADF-STEM. In particular, when the shell is amorphous, the shell thickness, which is easily observed as a part different from the core, can be easily determined with HAADF-STEM. When the shell thickness is not constant, the smallest thickness is taken as the shell thickness of the particle.
[0076] Alternatively, the average particle size of the core may be measured in advance before coating with the shell, and the thickness of the shell may be determined by measuring the average particle size of the core-shell semiconductor nanoparticles and calculating the difference between the average particle size and the previously measured average particle size of the core.
[0077] The core-shell type semiconductor nanoparticles preferably have a substantially tetragonal crystal structure. The crystal structure is identified by measuring the XRD pattern obtained by X-ray diffraction (XRD) analysis as described above. The term "substantially tetragonal" means that the ratio of the peak height at about 48°, which indicates hexagonal and orthorhombic crystals, to the main peak at about 26°, which indicates tetragonal crystals, is 10% or less.
[0078] When irradiated with ultraviolet light, visible light, infrared light, or other light, the core-shell type semiconductor nanoparticles emit light with a longer wavelength than the irradiated light. Specifically, when irradiated with ultraviolet light, visible light, or infrared light, the semiconductor nanoparticles can emit light with a longer wavelength than the irradiated light, and with a main component emission lifetime of 200 ns or less and / or an emission spectrum half width of 70 nm or less.
[0079] Core-shell type semiconductor nanoparticles containing semiconductor nanoparticles containing Ag, at least one of In and Ga, and S in the core emit light with an emission peak wavelength in the range of 500 nm to 600 nm by irradiating light having a peak near 450 nm. The half width of the emission peak in the emission spectrum may be, for example, 70 nm or less, 60 nm or less, 55 nm or less, or 50 nm or less. The lower limit of the half width may be, for example, 10 nm or more or 20 nm or more. The half width may be, for example, 250 meV or less, 210 meV or less, or 190 meV or less. The lower limit of the half width may be, for example, 35 meV or more, or 70 meV or more. For example, when the semiconductor nanoparticles contained in the core are Ag-In-Ga-S or Ag-Ga-S in which part or all of In, which is a group 13 element, is replaced with Ga, which is also a group 13 element, in Ag-In-S, the emission peak shifts to the short wavelength side.
[0080] The core-shell type semiconductor nanoparticles of the fourth embodiment include a core containing semiconductor nanoparticles containing Ag and Cu, at least one of In and Ga, and S, in which the ratio of the number of Cu atoms to the total number of Ag and Cu atoms is 0.001 or more and 0.9 or less, and a shell arranged on the surface of the core and substantially consisting of a group 13 element and a group 16 element. The core-shell type semiconductor nanoparticles of the fourth embodiment emit light having an emission peak wavelength in the range of 500 nm to 820 nm by irradiating them with light having a wavelength in the range of 350 nm to less than 500 nm, for example, light having a peak around 450 nm. The half width of the emission peak in the emission spectrum may be, for example, 70 nm or less, 60 nm or less, 55 nm or less, or 50 nm or less. The lower limit of the half width may be, for example, 10 nm or more or 20 nm or more. The half width may be, for example, 250 meV or less, 210 meV or less, or 190 meV or less. The lower limit of the half width may be, for example, 35 meV or more, or 70 meV or more. For example, when the semiconductor nanoparticles contained in the core are Ag-Cu-In-Ga-S or Ag-Cu-Ga-S in which part or all of In, a group 13 element, is replaced with Ga, a group 13 element, in Ag-Cu-In-S, the emission peak shifts to the short wavelength side. Also, when the ratio of the number of moles of Cu to the total number of moles of Ag and Cu increases, the emission peak shifts to the long wavelength side.
[0081] The emission of the core-shell semiconductor nanoparticles may include defect emission (e.g., donor-acceptor emission) in addition to band-edge emission, but is preferably substantially band-edge emission only. Defect emission generally has a long emission lifetime and a broad spectrum, with its peak at a longer wavelength side than band-edge emission. Here, being substantially band-edge emission only means that the purity of the band-edge emission component in the emission spectrum is 40% or more, preferably 60% or more. The "purity of the band-edge emission component" is expressed by the following formula when the peak of the emission spectrum is separated into two peaks, a band-edge emission peak and a defect emission peak, and their areas are a1 and a2, respectively. It is assumed that the shape of each peak is a normal distribution. Purity of band edge emission component (%) = a1 / (a1+a2)×100 If the emission spectrum does not contain any band-edge emission at all, i.e., if it contains only defect emission, it is 0%. If the peak areas of the band-edge emission and defect emission are the same, it is 50%. If it contains only band-edge emission, it is 100%.
[0082] The quantum yield of band edge emission is measured using a quantum yield measurement device at an excitation wavelength of 450 nm and a temperature of 25° C., and is defined as the internal quantum yield calculated in the range of 506 nm to 882 nm multiplied by the purity of the band edge emission component and divided by 100. The quantum yield of band edge emission of core-shell semiconductor nanoparticles is, for example, 10% or more, and preferably 20% or more.
[0083] The position of the peak of the band edge emission emitted by the core-shell semiconductor nanoparticles can be changed by changing the particle size of the core-shell semiconductor nanoparticles. For example, when the particle size of the core-shell semiconductor nanoparticles is made smaller, the peak wavelength of the band edge emission tends to shift to the shorter wavelength side. Furthermore, when the particle size of the core-shell semiconductor nanoparticles is made smaller, the half width of the spectrum of the band edge emission tends to become smaller.
[0084] It is also preferred that the core-shell semiconductor nanoparticles have an exciton peak in their absorption spectrum or excitation spectrum (also called the fluorescence excitation spectrum). The exciton peak is a peak obtained by exciton generation, and the fact that it appears in the absorption spectrum or excitation spectrum means that the particle size distribution is small and that the particles are suitable for band edge emission with few crystal defects. The steeper the exciton peak, the more particles with uniform particle size and few crystal defects are contained in the core-shell semiconductor nanoparticle aggregate. Therefore, the half-width of the emission is narrowed, and it is expected that the emission efficiency is improved. In the absorption spectrum or excitation spectrum of the core-shell semiconductor nanoparticles, the exciton peak is observed, for example, within the range of 350 nm to 1000 nm. The excitation spectrum for observing the presence or absence of the exciton peak may be measured by setting the observation wavelength near the peak wavelength.
[0085] The shell surface of the core-shell semiconductor nanoparticles may be modified with a surface modifier. Specific examples of the surface modifier include nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, and oxygen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, as well as compounds containing phosphorus having a negative oxidation number (hereinafter also referred to as "specific modifier"). When the surface modifier of the shell contains the specific modifier, the quantum yield of the band edge emission of the core-shell semiconductor nanoparticles is further improved.
[0086] The specific modifier contains P, which has a negative oxidation number as a Group 15 element. The oxidation number of P is -1 when one hydrogen atom or a hydrocarbon group is bonded to P, and +1 when one oxygen atom is bonded to P via a single bond, and changes depending on the substitution state of P. For example, the oxidation number of P in trialkylphosphine and triarylphosphine is -3, and in trialkylphosphine oxide and triarylphosphine oxide, it is -1.
[0087] The specific modifier may contain, in addition to P having a negative oxidation number, other Group 15 elements. Examples of other Group 15 elements include N, As, and Sb.
[0088] The specific modifying agent may be, for example, a phosphorus-containing compound having a hydrocarbon group having 4 to 20 carbon atoms. Examples of the hydrocarbon group having 4 to 20 carbon atoms include linear or branched saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, ethylhexyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl groups; linear or branched unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl groups; aromatic hydrocarbon groups such as phenyl and naphthyl groups; and arylalkyl groups such as benzyl and naphthylmethyl groups. Of these, saturated aliphatic hydrocarbon groups and unsaturated aliphatic hydrocarbon groups are preferred. When the specific modifying agent has a plurality of hydrocarbon groups, they may be the same or different.
[0089] Specific examples of the specific modifying agent include tributylphosphine, triisobutylphosphine, tripentylphosphine, trihexylphosphine, trioctylphosphine, tris(ethylhexyl)phosphine, tridecylphosphine, tridodecylphosphine, tritetradecylphosphine, trihexadecylphosphine, trioctadecylphosphine, triphenylphosphine, tributylphosphine oxide, triisobutylphosphine oxide, tripentylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, tris(ethylhexyl)phosphine oxide, tridecylphosphine oxide, tridodecylphosphine oxide, tritetradecylphosphine oxide, trihexadecylphosphine oxide, trioctadecylphosphine oxide, and triphenylphosphine oxide. At least one selected from the group consisting of these is preferred.
[0090] The surface of the shell may be modified with other surface modifiers in addition to the specific modifier. Examples of other surface modifiers include nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, and oxygen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms. Examples of nitrogen-containing compounds include amines and amides, examples of sulfur-containing compounds include thiols, and examples of oxygen-containing compounds include fatty acids.
[0091] As other surface modifiers, nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms and sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms are preferred. Examples of nitrogen-containing compounds include alkylamines such as n-butylamine, isobutylamine, n-pentylamine, n-hexylamine, octylamine, decylamine, dodecylamine, tetradecylamine, hexadecylamine, and octadecylamine, and alkenylamines such as oleylamine. In particular, n-tetradecylamine is preferred because it is easy to obtain a compound with high purity and has a boiling point of more than 290°C. Examples of sulfur-containing compounds include n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, and octadecanethiol.
[0092] The surface modifier may be used in combination of two or more different types. For example, one compound selected from the nitrogen-containing compounds exemplified above (e.g., oleylamine) and one compound selected from the sulfur-containing compounds exemplified above (e.g., dodecanethiol) may be used in combination.
[0093] The emission of the core-shell type semiconductor nanoparticles modified with a surface modifier may include defect emission (donor-acceptor emission) in addition to band edge emission, but is preferably substantially band edge emission only. Substantially band edge emission only is as described above for the core-shell type semiconductor nanoparticles, and the purity of the band edge emission component is preferably 60% or more.
[0094] The quantum yield of band edge emission of the core-shell type semiconductor nanoparticles modified with a surface modifier is measured as described above for the core-shell type semiconductor nanoparticles, and the quantum yield of band edge emission is, for example, 30% or more, preferably 40% or more, and particularly preferably 50% or more.
[0095] The core-shell type semiconductor nanoparticles can be produced, for example, as follows: The method for producing core-shell type semiconductor nanoparticles includes a preparation step of obtaining a second mixture by mixing a dispersion liquid containing semiconductor nanoparticles obtained by the above-mentioned method for producing semiconductor nanoparticles, a compound containing a Group 13 element, and a simple substance of a Group 16 element or a compound containing a Group 16 element, and a shell formation step of heat-treating the second mixture.
[0096] In the liquid in which the semiconductor nanoparticles are dispersed, no scattered light occurs, and the dispersion is generally obtained as a transparent (colored or colorless) one. The solvent for dispersing the semiconductor nanoparticles can be any organic solvent, as in the case of producing the semiconductor nanoparticles. The organic solvent can be a surface modifier or a solution containing a surface modifier. For example, the organic solvent can be at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms (e.g., amine-based solvents), which are surface modifiers described in relation to the method for producing semiconductor nanoparticles. The organic solvent can be at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms (e.g., thiol-based solvents). The organic solvent can be a combination of at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms and at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms. The nitrogen-containing compounds are preferred because they are particularly easy to obtain in high purity and have a boiling point of more than 290° C., which is higher than the reaction temperature. Specific organic solvents include oleylamine, n-tetradecylamine, dodecanethiol, and combinations thereof.
[0097] The solvent for dispersing the semiconductor nanoparticles may contain a halogen-based solvent such as chloroform, or may be substantially a halogen-based solvent. In addition, after dispersing the semiconductor nanoparticles in a halogen-based solvent, the solvent may be exchanged with an organic solvent containing a surface modifier such as a nitrogen-containing compound to obtain a dispersion of the semiconductor nanoparticles. The solvent exchange can be performed, for example, by adding a surface modifier to a dispersion of the semiconductor nanoparticles containing a halogen-based solvent, and then removing at least a part of the halogen-based solvent. Specifically, for example, a dispersion containing a halogen-based solvent and a surface modifier can be heat-treated under reduced pressure to remove at least a part of the halogen-based solvent, thereby obtaining a dispersion of the semiconductor nanoparticles containing the surface modifier. The reduced pressure conditions and the heat treatment temperature in the heat treatment under reduced pressure may be conditions under which at least a part of the halogen-based solvent is removed and the surface modifier remains. Specifically, the reduced pressure conditions may be, for example, 1 Pa or more and 2000 Pa or less, and preferably 50 Pa or more and 500 Pa or less. In addition, the heat treatment temperature may be, for example, 20°C or more and 120°C or less, and preferably 50°C or more and 80°C or less.
[0098] The semiconductor nanoparticle dispersion has a particle concentration of, for example, 5.0×10 -7 mol / L or more 5.0×10 -5 mol / L or less, especially 1.0×10 -6 mol / L or more, 1.0×10 -5 The concentration may be adjusted to be less than mol / L. If the ratio of particles in the dispersion is too small, it becomes difficult to recover the product by the aggregation and precipitation process in a poor solvent, and if it is too large, the ratio of Ostwald ripening of the material that constitutes the core and fusion due to collision increases, and the particle size distribution tends to become broad. Note that the particle concentration is based on the amount of substance as particles (number of particles).
[0099] The compound containing a Group 13 element is a source of the Group 13 element, and is, for example, an organic salt, an inorganic salt, or an organometallic compound of the Group 13 element. Examples of the compound containing a Group 13 element include nitrates, acetates, sulfates, hydrochlorides, sulfonates, and acetylacetonate complexes, and are preferably organic salts such as acetates, or organometallic compounds. This is because organic salts and organometallic compounds have high solubility in organic solvents, and tend to allow the reaction to proceed more uniformly.
[0100] A simple substance of a group 16 element or a compound containing a group 16 element is a source of the group 16 element. For example, when sulfur (S) is used as a constituent element of the shell as the group 16 element, simple sulfur such as high purity sulfur can be used. Alternatively, sulfur-containing compounds such as thiols such as n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, and octadecanethiol, disulfides such as dibenzyl sulfide, thiourea, alkylthioureas such as 1,3-dimethylthiourea, and thiocarbonyl compounds can be used. Among them, when alkylthioureas such as 1,3-dimethylthiourea are used as a source of a group 16 element (sulfur source), a shell is sufficiently formed, and semiconductor nanoparticles that give strong band edge emission can be easily obtained.
[0101] When oxygen (O) is used as the group 16 element for the shell, alcohols, ethers, carboxylic acids, ketones, and N-oxide compounds may be used as the group 16 element source. When selenium (Se) is used as the group 16 element for the shell, simple selenium, selenized phosphine oxide, organic selenium compounds (dibenzyl diselenide and diphenyl diselenide), hydrides, and other compounds may be used as the group 16 element source. When tellurium (Te) is used as the group 16 element for the shell, simple tellurium, tellurized phosphine oxide, and hydrides may be used as the group 16 element source.
[0102] As a method for producing core-shell semiconductor nanoparticles, the dispersion liquid containing semiconductor nanoparticles is heated until the peak temperature is 200°C or more and 310°C or less, and after the peak temperature is reached, a mixed liquid in which a Group 13 element source and a Group 16 element source are dispersed or dissolved in an organic solvent is added little by little while the peak temperature is maintained, and then the temperature is lowered to form the shell layer (slow injection method). In this case, the heat treatment is started immediately after the dispersion liquid containing semiconductor nanoparticles and the mixed liquid are mixed to obtain a second mixture. The mixed liquid may be added at a rate of 0.1 mL / hour to 10 mL / hour, particularly 1 mL / hour to 5 mL / hour. The peak temperature may be maintained as necessary even after the addition of the mixed liquid is completed.
[0103] If the peak temperature is above the above temperature, the surface modifier modifying the semiconductor nanoparticles is sufficiently removed, or the chemical reaction for shell formation proceeds sufficiently, so that the semiconductor layer (shell) tends to be formed sufficiently. If the peak temperature is below the above temperature, the semiconductor nanoparticles are prevented from being altered, and good band edge emission tends to be obtained. The time for holding the peak temperature can be a total of 1 minute to 300 minutes, particularly 10 minutes to 120 minutes, from the start of addition of the mixed liquid. The holding time of the peak temperature is selected in relation to the peak temperature, and if the holding time is longer when the peak temperature is lower, and if the holding time is shorter when the peak temperature is higher, a good shell layer is likely to be formed. The rate of temperature increase and the rate of temperature decrease are not particularly limited, and the temperature decrease may be performed, for example, by holding the peak temperature for a predetermined time, stopping heating by a heating source (e.g., an electric heater), and allowing to cool.
[0104] Alternatively, as a method for producing core-shell type semiconductor nanoparticles, a dispersion liquid containing semiconductor nanoparticles may be mixed with a Group 13 element source and a Group 16 element source to obtain a second mixture, and then the second mixture may be heat-treated to form a semiconductor layer, which is a shell, on the surface of the semiconductor nanoparticles (heating-up method). Specifically, the second mixture may be gradually heated to a peak temperature of 200°C or more and 310°C or less, and may be heated in such a manner that the peak temperature is maintained for 1 minute to 300 minutes, and then the temperature is gradually lowered. The heating rate may be, for example, 1°C / min to 50°C / min, but in order to minimize the deterioration of the core caused by continued heat treatment in the absence of a shell, it is preferable that the heating rate is 50°C / min to 100°C / min up to 200°C. In addition, when the temperature is further raised to 200°C or more, it is preferable that the heating rate thereafter is 1°C / min to 5°C / min. The heating rate may be, for example, 1°C / min to 50°C / min. The advantages of the peak temperature being within the above range are as explained in the slow injection method.
[0105] The heating-up method tends to produce core-shell type semiconductor nanoparticles that give stronger band edge emission than when the shell is formed by the slow injection method.
[0106] The second mixture in the heating-up method may be prepared by mixing a dispersion of semiconductor nanoparticles containing a halogen-based solvent, an organic solvent such as a surface modifier, and a Group 13 element source and a Group 16 element source, and then removing at least a part of the halogen-based solvent, for example, by heat treatment under reduced pressure. That is, the preparation step may include mixing a dispersion of semiconductor nanoparticles containing a halogen-based solvent, an organic solvent such as a surface modifier, and a Group 13 element source and a Group 16 element source to obtain a pre-mixture, and removing at least a part of the halogen-based solvent from the pre-mixture to obtain a second mixture.
[0107] In either method, the ratio of the Group 13 element source and the Group 16 element source may be determined in accordance with the stoichiometric composition ratio of the compound semiconductor composed of the Group 13 element and the Group 16 element, but it does not necessarily have to be the stoichiometric composition ratio. For example, the ratio of the Group 16 element to the Group 13 element may be 0.75 or more and 1.5 or less.
[0108] Furthermore, the amounts of the Group 13 element source and the Group 16 element source are selected in consideration of the amount of semiconductor nanoparticles contained in the dispersion so that a shell of the desired thickness is formed on the semiconductor nanoparticles present in the dispersion. For example, the amounts of the Group 13 element source and the Group 16 element source may be determined so that 1 μmol to 10 mmol, particularly 5 μmol to 1 mmol, of a compound semiconductor having a stoichiometric composition consisting of a Group 13 element and a Group 16 element is generated per 10 nmol of substance as particles of the semiconductor nanoparticles. However, the substance amount as particles is the molar amount when one particle is regarded as a giant molecule, and the number of semiconductor nanoparticles contained in the dispersion is determined by Avogadro's number (NA=6.022×10 23 ) divided by
[0109] In the method for producing core-shell semiconductor nanoparticles, it is preferable to form a shell containing indium sulfide or gallium sulfide by using indium acetate or gallium acetylacetonate as the Group 13 element source, elemental sulfur, thiourea or dibenzyl disulfide as the Group 16 element source, and a mixture of oleylamine and dodecanethiol or oleylamine as the dispersion medium.
[0110] In addition, when a mixture of oleylamine and dodecanethiol or oleylamine is used as the dispersion liquid in the heating-up method, core-shell type semiconductor nanoparticles tend to be obtained that give an emission spectrum in which the intensity of the broad peak derived from defect emission is sufficiently smaller than the intensity of the peak of band edge emission. The above tendency is also significantly observed when a gallium source is used as the Group 13 element source.
[0111] In this way, the shell is formed to form the core-shell type semiconductor nanoparticles having the core-shell structure. The obtained core-shell type semiconductor nanoparticles having the core-shell structure may be separated from the solvent, and may be further purified and dried as necessary. The methods of separation, purification and drying are as described above in relation to the semiconductor nanoparticles, and therefore detailed description thereof will be omitted here.
[0112] When the shell surface of the core-shell semiconductor nanoparticles is modified with a specific modifying agent, the core-shell semiconductor nanoparticles obtained above may be subjected to a modification step. In the modification step, the core-shell semiconductor nanoparticles are contacted with a specific modifying agent containing phosphorus (P) having a negative oxidation number to modify the shell surface of the core-shell semiconductor particles. This produces core-shell semiconductor nanoparticles that exhibit band edge emission with a better quantum yield.
[0113] The contact between the core-shell type semiconductor nanoparticles and the specific modifier can be carried out, for example, by mixing a dispersion of the core-shell type semiconductor nanoparticles with the specific modifier. The core-shell type semiconductor particles may also be mixed with a liquid specific modifier. The specific modifier may be used in its solution. The dispersion of the core-shell type semiconductor nanoparticles can be obtained by mixing the core-shell type semiconductor nanoparticles with a suitable organic solvent. Examples of the organic solvent used for dispersion include halogenated solvents such as chloroform; aromatic hydrocarbon solvents such as toluene; and aliphatic hydrocarbon solvents such as cyclohexane, hexane, pentane, and octane. The concentration of the substance amount in the dispersion of the core-shell type semiconductor nanoparticles is, for example, 1×10 -7 mol / L or more 1×10 -3 mol / L or less, preferably 1×10 -6 mol / L or more 1×10 -4 mol / L or less.
[0114] The amount of the specific modifier used relative to the core-shell type semiconductor nanoparticles may be, for example, 1 to 50,000 times in terms of molar ratio. -7 mol / L or more 1.0×10-3 When a dispersion of core-shell type semiconductor nanoparticles having a concentration of mol / L or less is used, the dispersion and the specific modifying agent may be mixed at a volume ratio of 1:1000 to 1000:1.
[0115] The temperature during contact between the core-shell semiconductor nanoparticles and the specific modifying agent may be, for example, -100°C or more and 100°C or less, or 30°C or more and 75°C or less. The contact time may be appropriately selected depending on the amount of the specific modifying agent used, the concentration of the dispersion liquid, and the like. The contact time may be, for example, 1 minute or more, preferably 1 hour or more, and may be 100 hours or less, preferably 48 hours or less. The atmosphere during contact may be, for example, an inert gas atmosphere such as nitrogen gas or a rare gas.
[0116] Light-emitting devices The light-emitting device includes a light conversion member and a semiconductor light-emitting element, and the light conversion member contains the semiconductor nanoparticles or core-shell type semiconductor nanoparticles described above. According to this light-emitting device, for example, a part of the light emitted from the semiconductor light-emitting element is absorbed by the semiconductor nanoparticles or the semiconductor nanoparticles with a core-shell structure, and light with a longer wavelength is emitted. Then, the light from the semiconductor nanoparticles or the semiconductor nanoparticles with a core-shell structure and the remaining part of the light emitted from the semiconductor light-emitting element are mixed, and the mixed light can be used as the light emitted by the light-emitting device.
[0117] Specifically, a light-emitting device that emits white light can be obtained by using a semiconductor light-emitting element that emits blue-violet light or blue light with a peak wavelength of about 400 nm or more and 490 nm or less, and a semiconductor nanoparticle or a core-shell semiconductor nanoparticle that absorbs blue light and emits yellow light. Alternatively, a white light-emitting device can be obtained by using two types of semiconductor nanoparticles or core-shell semiconductor nanoparticles, one that absorbs blue light and emits green light, and the other that absorbs blue light and emits red light.
[0118] Alternatively, a white light-emitting device can be obtained by using a semiconductor light-emitting element that emits ultraviolet light with a peak wavelength of 400 nm or less, and three types of semiconductor nanoparticles or core-shell structured semiconductor nanoparticles that absorb the ultraviolet light and emit blue light, green light, and red light, respectively. In this case, it is desirable to have all the light from the light-emitting element absorbed and converted by the semiconductor nanoparticles so that the ultraviolet light emitted from the light-emitting element does not leak to the outside.
[0119] Alternatively, by using a material that emits blue-green light with a peak wavelength of approximately 490 nm or more and 510 nm or less, and using semiconductor nanoparticles or semiconductor nanoparticles with a core-shell structure that absorb the blue-green light and emit red light, a device that emits white light can be obtained.
[0120] Alternatively, a semiconductor light-emitting element that emits visible light, for example, red light having a wavelength of 700 nm or more and 780 nm or less, is used. If semiconductor nanoparticles or core-shell semiconductor nanoparticles that absorb visible light and emit near-infrared light are used, a light-emitting device that emits near-infrared light can be obtained.
[0121] The semiconductor nanoparticles or core-shell semiconductor nanoparticles may be used in combination with other semiconductor quantum dots, or may be used in combination with other phosphors that are not quantum dots (e.g., organic phosphors or inorganic phosphors). Other semiconductor quantum dots are, for example, binary semiconductor quantum dots described in the Background Art section. As phosphors that are not quantum dots, garnet phosphors such as aluminum garnet phosphors can be used. Garnet phosphors include yttrium-aluminum-garnet phosphors activated with cerium, and lutetium-aluminum-garnet phosphors activated with cerium. Other examples include nitrogen-containing calcium aluminosilicate phosphors activated with europium and / or chromium, silicate phosphors activated with europium, β-SiAlON phosphors, nitride phosphors such as CASN or SCASN, and LnSi3N 11rare earth nitride phosphors such as BaSi2O2N2:Eu or Ba3Si6O 12 Examples of phosphors that can be used include oxynitride phosphors such as N2:Eu, sulfide phosphors such as CaS, SrGa2S4, SrAl2O4, and ZnS, chlorosilicate phosphors, SrLiAl3N4:Eu phosphors, SrMg3SiN4:Eu phosphors, and K2SiF6:Mn phosphors as manganese-activated fluoride complex phosphors.
[0122] In a light-emitting device, the light conversion member containing semiconductor nanoparticles or semiconductor nanoparticles with a core-shell structure may be, for example, a sheet or plate-like member, or may be a member having a three-dimensional shape. An example of a member having a three-dimensional shape is a sealing member formed in a surface-mounted light-emitting diode by filling a resin into a recess formed in a package in which a semiconductor light-emitting element is disposed on the bottom surface of the recess to seal the light-emitting element.
[0123] Another example of the light conversion member is a resin member formed to surround the upper and side surfaces of the semiconductor light emitting element with a substantially uniform thickness when the semiconductor light emitting element is disposed on a planar substrate. Still another example of the light conversion member is a resin member formed in a plate shape with a predetermined thickness on the upper part of the semiconductor light emitting element and the resin member containing the reflector when the semiconductor light emitting element is surrounded by a resin member containing a reflector so that the upper end of the resin member is flush with the semiconductor light emitting element.
[0124] The light conversion member may be in contact with the semiconductor light emitting element, or may be provided at a distance from the semiconductor light emitting element. Specifically, the light conversion member may be a pellet-shaped member, a sheet member, a plate-shaped member, or a rod-shaped member that is disposed at a distance from the semiconductor light emitting element, or may be a member provided in contact with the semiconductor light emitting element, such as a sealing member, a coating member (a member that covers the light emitting element and is provided separately from the molding member), or a molding member (including, for example, a member having a lens shape).
[0125] In addition, in the case where two or more types of semiconductor nanoparticles or core-shell structured semiconductor nanoparticles that emit light of different wavelengths are used in a light-emitting device, the two or more types of semiconductor nanoparticles or core-shell type semiconductor nanoparticles may be mixed in one light conversion member, or two or more light conversion members containing only one type of semiconductor nanoparticles or core-shell type semiconductor nanoparticles may be combined and used. In this case, the two or more types of light conversion members may form a laminated structure or may be arranged in a dot-like or stripe-like pattern on a plane.
[0126] An example of the semiconductor light-emitting element is an LED chip. The LED chip may have a semiconductor layer made of one or more materials selected from the group consisting of GaN, GaAs, InGaN, AlInGaP, GaP, SiC, ZnO, etc. A semiconductor light-emitting element that emits blue-violet light, blue light, or ultraviolet light may have a composition of, for example, In. X Al Y Ga 1-X-Y The semiconductor layer is made of a GaN-based compound represented by N (0≦X, 0≦Y, X+Y<1).
[0127] The light-emitting device of this embodiment is preferably incorporated into a liquid crystal display device as a light source. Since the band-edge emission by semiconductor nanoparticles or semiconductor nanoparticles with a core-shell structure has a short emission life, a light-emitting device using the same is suitable for a light source of a liquid crystal display device that requires a relatively fast response speed. In addition, the semiconductor nanoparticles or semiconductor nanoparticles with a core-shell structure of this embodiment can exhibit an emission peak with a small half-width as the band-edge emission. Therefore, the light-emitting device may have the following aspects. (1) A blue semiconductor light-emitting element is used to obtain blue light having a peak wavelength in the range of 420 nm to 490 nm, and a semiconductor nanoparticle or a core-shell type semiconductor nanoparticle is used to obtain green light having a peak wavelength in the range of 510 nm to 550 nm, preferably 530 nm to 540 nm, and a red light having a peak wavelength in the range of 600 nm to 680 nm, preferably 630 nm to 650 nm. (2) A semiconductor light emitting element is used to obtain ultraviolet light having a peak wavelength of 400 nm or less, and semiconductor nanoparticles or core-shell semiconductor nanoparticles are used to obtain blue light having a peak wavelength of 430 nm to 470 nm, preferably 440 nm to 460 nm, green light having a peak wavelength of 510 nm to 550 nm, preferably 530 nm to 540 nm, and red light having a peak wavelength of 600 nm to 680 nm, preferably 630 nm to 650 nm. By configuring such a light emitting device, a liquid crystal display device with good color reproducibility can be obtained without using a dark color filter. The light emitting device may be used, for example, as a direct type backlight or an edge type backlight.
[0128] Alternatively, a sheet, plate-like member, or rod made of resin, glass, or the like, containing semiconductor nanoparticles or core-shell type semiconductor nanoparticles may be incorporated into a liquid crystal display device as a light conversion member independent of the light emitting device. EXAMPLES
[0129] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0130] Example 1 Synthesis of semiconductor nanoparticles In a reaction vessel, 0.4 mmol of silver acetate (AgOAc) and 0.4 mmol of indium acetate (In(OAc)3) were mixed with 8 mL of distilled and purified oleylamine (OLA), and dodecanethiol (1.25 mmol, 300 μL) was added to obtain liquid A. Separately, 0.8 mmol of 1,3-dimethylthiourea was dissolved in 2 mL of oleylamine to obtain liquid B. Liquid A was degassed and replaced with an argon atmosphere, and heated to 140°C. Liquid B was then added dropwise to liquid A over 30 minutes. The rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture was 0.067 / min. After the dropwise addition, the liquid temperature was kept at 140°C for 30 minutes. The mixture was then allowed to cool to room temperature, and coarse particles were removed by centrifugation, after which methanol was added to the supernatant to precipitate the semiconductor nanoparticles that would become the cores, which were then collected by centrifugation. The collected solid was dispersed in 2 mL of oleylamine.
[0131] The X-ray diffraction (XRD) pattern of the obtained semiconductor nanoparticles was measured and compared with that of tetragonal (chalcopyrite type) AgInS2 and orthorhombic AgInS2. The measured XRD pattern is shown in Figure 1. From the XRD pattern, it was confirmed that the crystal structure of the obtained semiconductor nanoparticles was substantially the same as that of tetragonal AgInS2, since no peak was observed around 48°, which is seen in orthorhombic crystals. The XRD pattern was measured using a powder X-ray diffractometer (trade name SmartLab) manufactured by Rigaku Corporation.
[0132] The shape of the obtained semiconductor nanoparticles was observed using a transmission electron microscope (TEM, Hitachi High-Technologies Corporation, product name H-7650), and the average particle size was measured from TEM images at 80,000 to 200,000 magnifications. Here, a Hi-Res Carbon HRC-C10 STEM Cu100P grid (Oken Shoji Co., Ltd.) was used as the TEM grid. The shape of the obtained particles is considered to be spherical or polygonal. The average particle size was determined by selecting TEM images from three or more locations, measuring the particle size of all measurable nanoparticles contained therein, that is, all particles except those whose particle images are cut off at the edge of the image, and calculating the arithmetic average. In both the examples and the comparative examples described later, the particle size of a total of 100 or more nanoparticles was measured using three or more TEM images. The average particle size of the semiconductor nanoparticles was 4.68 nm, with a standard deviation of 0.36 nm.
[0133] The amount of indium contained in the obtained semiconductor nanoparticles was determined by ICP emission spectroscopy (Shimadzu Corporation, ICPS-7510) and found to be 43.5 μmol. The volume of the semiconductor nanoparticles with an average particle size of 4.68 nm was 53.67 nm when spherical. 3 The unit cell volume of a tetragonal silver indium sulfide crystal is 0.38 nm 3 (lattice constants 0.528 nm, 0.5828 nm, 1.119 nm), and by dividing the volume of the semiconductor nanoparticle by the unit lattice volume, it was calculated that one semiconductor nanoparticle contains 141 unit lattices. Next, since one unit lattice of a tetragonal silver indium sulfide crystal contains four indium atoms, it was calculated that one nanoparticle contains 564 indium atoms. By dividing the amount of indium by the number of indium atoms per nanoparticle, the amount of substance of the semiconductor nanoparticle as nanoparticles was calculated to be 77.1 nmol.
[0134] Synthesis of core-shell semiconductor nanoparticles 0.1 mmol of gallium acetylacetonate (Ga(acac)3) and 0.1 mmol of 1,3-dimethylthiourea were measured and added to 8 mL of distilled and purified oleylamine, and then the oleylamine dispersion of the semiconductor nanoparticles synthesized above was added as a dispersion of core particles in an amount equivalent to 30 nmol in terms of nanoparticle concentration. The resulting solution was degassed at about 60°C and replaced with an argon atmosphere, and then rapidly heated to 230°C (heating rate of about 60°C / min), and after 230°C, the temperature was further raised to 280°C at a rate of 2°C / min, and heat-treated at 280°C for 30 minutes. The solution was then allowed to cool to room temperature, methanol was added to precipitate the core-shell type semiconductor particles, and the resulting core-shell type semiconductor nanoparticles were dispersed in chloroform after washing.
[0135] Modification process A portion of the obtained chloroform dispersion of core-shell semiconductor nanoparticles was taken, and an equal amount of trioctylphosphine (TOP) was added and mixed, and then the mixture was allowed to stand at room temperature for 24 hours to obtain a dispersion of TOP-modified core-shell semiconductor nanoparticles.
[0136] Measurement of absorption, emission spectra and quantum yield The absorption and emission spectra of the semiconductor nanoparticles, the core-shell type semiconductor nanoparticles, and the TOP-modified core-shell type semiconductor nanoparticles were measured. The results are shown in Figures 2 and 3. The absorption spectrum was measured using an ultraviolet-visible near-infrared spectrophotometer (manufactured by JASCO, product name V-670) in the wavelength range of 350 nm to 850 nm. The emission spectrum was measured using a multichannel spectrometer (manufactured by Hamamatsu Photonics, product name PMA12) at an excitation wavelength of 450 nm. The quantum yield was measured using a fluorescence spectrum measuring device PMA-12 (manufactured by Hamamatsu Photonics) equipped with an integrating sphere at room temperature (25°C) and an excitation wavelength of 450 nm in the wavelength range of 350 nm to 1100 nm, and calculated from the wavelength range of 506 nm to 882 nm.
[0137] As shown in Figure 2, a slight shoulder was observed in the absorption spectrum of the core-shell semiconductor nanoparticles at around 500 nm, and it was confirmed that there was almost no absorption from around 600 nm onwards, suggesting that there is an exciton peak at around 400 nm to 600 nm. In addition, as shown in Figure 3, band edge emission with a half width of about 42 nm was observed at around 579 nm, the quantum yield of the band edge emission was 10.3%, and the purity of the band edge emission component was 42.7%. In addition, in the emission spectrum of the TOP-modified core-shell semiconductor nanoparticles, band edge emission with a half width of about 40 nm was observed at around 579 nm, the quantum yield of the band edge emission was 37.4%, and the purity of the band edge emission component was 62.3%.
[0138] Comparative Example 1 Synthesis of semiconductor nanoparticles In a reaction vessel, 0.4 mmol of silver acetate (AgOAc) and 0.4 mmol of indium acetate (In(OAc)3) were mixed with 8 mL of distilled and purified oleylamine (OLA), and dodecanethiol (1.25 mmol, 300 μL) was added while stirring. The synthesis solution was degassed and replaced with an argon atmosphere, and the temperature was raised to approximately 70°C. The lid was opened once, and thiourea crystals (0.8 mmol, 60.8 mg) were added at once within 10 seconds to obtain a mixture. The rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture was 12 / min or more. Next, degassing was performed for a very short time, and the temperature was raised at a heating rate of 30°C / min until it reached 130°C. After reaching 130°C by actual measurement, the heat treatment was continued for 600 seconds. The reaction vessel was then immersed in room temperature water and quenched to stop the synthesis. During quenching, the temperature was lowered at an average rate of about 50°C / min. After removing coarse particles by centrifugation, methanol was added to the supernatant to precipitate the core semiconductor nanoparticles, which were then collected by centrifugation. The collected solid was dispersed in 2 mL of oleylamine.
[0139] The XRD pattern of the obtained semiconductor nanoparticles was measured in the same manner as in the Example, and compared with that of tetragonal (chalcopyrite type) AgInS2 and orthorhombic AgInS2. The measured XRD pattern is shown in Figure 4. From the XRD pattern, the crystal structure of the semiconductor nanoparticles is substantially the same as that of tetragonal AgInS2, as in the Example (Figure 1), but a slight peak seen in orthorhombic crystals was observed around 48° compared with the Example.
[0140] The obtained semiconductor nanoparticles were observed using a transmission electron microscope in the same manner as in Example 1. The shape of the obtained particles was considered to be spherical or polygonal, similar to that in Example 1, and the average particle size was 4.17 nm with a standard deviation of 0.45 nm.
[0141] The amount of indium contained in the resulting semiconductor nanoparticles was determined by ICP emission spectrometry in the same manner as in the Example, and was found to be 41.5 μmol. From the average particle size of 4.17 nm, the amount of indium contained in the semiconductor nanoparticles was calculated to be 104 nmol.
[0142] Synthesis of core-shell semiconductor nanoparticles 0.1 mmol of gallium acetylacetonate (Ga(acac)3) and 0.1 mmol of 1,3-dimethylthiourea were measured and added to 8 mL of distilled and purified oleylamine, and then 0.5 mL (the amount of substance, which is the number of particles as nanoparticles, is 30 nmol) of the oleylamine dispersion of the semiconductor nanoparticles synthesized above was added as a dispersion of core particles. The obtained solution was degassed at about 60°C, and then heated at a heating rate of 60°C / min until it reached 230°C, and after 230°C, it was heated at a rate of 2°C / min to 280°C, and heat-treated at 280°C for 30 minutes. Next, when the temperature was lowered to 150°C at room temperature, a vacuum was drawn once to remove volatile components such as hydrogen sulfide, and when the temperature reached 100°C or less, the flask was immersed in water and rapidly cooled to room temperature. Methanol was added to precipitate the core-shell particles, and after washing, the obtained core-shell type semiconductor nanoparticles were dispersed in chloroform (4 mL).
[0143] Modification process A part of the obtained chloroform dispersion of the core-shell type semiconductor nanoparticles was taken, and a dispersion of semiconductor nanoparticles that were TOP-modified core-shell particles was obtained in the same manner as in the Example.
[0144] Measurement of absorption, emission spectra and quantum yield The absorption and emission spectra of the semiconductor nanoparticles, the core-shell type semiconductor nanoparticles, and the TOP-modified core-shell type semiconductor nanoparticles were measured in the same manner as in the examples. The results are shown in Fig. 5 and Fig. 6. As shown in Fig. 5, a slight shoulder was observed in the absorption spectrum of the core-shell type semiconductor nanoparticles near 500 nm, and it was confirmed that there was almost no absorption from near 600 nm onwards, so it is inferred that there is an exciton peak near 400 nm to 600 nm. Also, as shown in Fig. 6, in the emission spectrum of the core-shell type semiconductor nanoparticles, band edge emission with a half width of about 44 nm was observed near 577 nm, the quantum yield of the band edge emission was 12.3%, and the purity of the band edge emission component was 44.4%. Also, in the emission spectrum of the TOP-modified core-shell type semiconductor nanoparticles, band edge emission with a half width of about 46 nm was observed near 579 nm, the quantum yield of the band edge emission was 31.7%, and the purity of the band edge emission component was 67.1%.
[0145] Example 2 Synthesis of semiconductor nanoparticles In a reaction vessel, 0.39 mmol of silver acetate (AgOAc), 0.01 mmol of copper (II) acetate (Cu(OAc)2), and 0.4 mmol of indium acetate (In(OAc)3) were mixed with 8 mL of distilled and purified oleylamine (OLA), and dodecanethiol (1.25 mmol, 300 μL) was added to prepare liquid A. Separately, 0.8 mmol of 1,3-dimethylthiourea was dissolved in 2 mL of oleylamine to prepare liquid B. Liquid A was degassed and replaced with an argon atmosphere, and heated to 140°C. Liquid B was then added dropwise to liquid A over 30 minutes. The rate of increase in the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture was 0.067 / min. After the completion of the dropwise addition, the liquid temperature was kept at 140°C for 30 minutes. It was then rapidly cooled to 50°C. After removing coarse particles by centrifugation, methanol was added to the supernatant to precipitate the core semiconductor nanoparticles, which were then collected by centrifugation. The collected solid was dispersed in 3 mL of oleylamine.
[0146] Synthesis of core-shell semiconductor nanoparticles 0.1 mmol of gallium acetylacetonate (Ga(acac)3) and 0.1 mmol of 1,3-dimethylthiourea were measured and added to 7 mL of distilled and purified oleylamine, and then the oleylamine dispersion of the semiconductor nanoparticles synthesized above was added as a dispersion of core particles in an amount equivalent to 30 nmol in terms of nanoparticle concentration. The resulting solution was degassed at about 80°C and replaced with an argon atmosphere, and then rapidly heated to 230°C (heating rate of about 60°C / min), and after 230°C, the temperature was further raised to 280°C at a rate of 2°C / min, and heat-treated at 280°C for 1 minute. It was then rapidly cooled to 50°C, methanol was added to precipitate the core-shell type semiconductor particles, and centrifugal separation was performed, after which the obtained core-shell type semiconductor nanoparticles were dispersed in chloroform.
[0147] Example 3 Synthesis of semiconductor nanoparticles and core-shell type semiconductor nanoparticles Semiconductor nanoparticles and core-shell type semiconductor nanoparticles were obtained in the same manner as in Example 2, except that the thiourea in the solution B was replaced with 1,3-dibutylthiourea.
[0148] Comparative Example 2 Synthesis of semiconductor nanoparticles 0.39 mmol of silver acetate (AgOAc), 0.01 mmol of copper acetate (Cu(OAc)2), and 0.4 mmol of indium acetate (In(OAc)3) were mixed with 8 mL of distilled and purified oleylamine (OLA) in a reaction vessel, and dodecanethiol (1.25 mmol, 300 μL) was added while stirring. The synthesis solution was degassed and replaced with an argon atmosphere, and the temperature was raised to approximately 70 ° C. The lid of the reaction vessel was opened once, and thiourea crystals (0.8 mmol, 60.8 mg) were added at once within 10 seconds to obtain a mixture (the increase rate of the ratio of the number of S atoms to the number of Ag atoms in the mixture was 12 / min or more). Next, degassing was performed for a short time, and the temperature was raised to 130 ° C. at a heating rate of 30 ° C. / min. After reaching 140 ° C. by actual measurement, the heat treatment was continued for 600 seconds. The reaction vessel was then immersed in room temperature water to rapidly cool. The temperature was decreased at an average rate of about 50°C / min during rapid cooling. After removing coarse particles by centrifugation, methanol was added to the supernatant to precipitate the semiconductor nanoparticles, which were then collected by centrifugation. The collected solid was dispersed in 3 mL of oleylamine.
[0149] Synthesis of core-shell semiconductor nanoparticles Core-shell type semiconductor nanoparticles were obtained in the same manner as in Example 2, except that the semiconductor nanoparticles obtained above were used.
[0150] The average particle size, absorption, and emission spectrum were measured for the semiconductor nanoparticles and core-shell type semiconductor nanoparticles obtained in Examples 2 and 3 and Comparative Example 2 in the same manner as in Example 1. The results are shown in Table 1 and Figures 7 to 10. The absorption spectrum was measured using an ultraviolet-visible near-infrared spectrophotometer (manufactured by JASCO, product name V-670) in the wavelength range of 350 nm to 850 nm. The emission spectrum was measured using a spectrofluorometer (manufactured by JASCO, product name FP-8600) at an excitation wavelength of 450 nm. The quantum yield was measured using a fluorescence spectrum measuring device PMA-12 (manufactured by Hamamatsu Photonics KK) equipped with an integrating sphere at room temperature (25°C) and an excitation wavelength of 450 nm in the wavelength range of 350 nm to 1100 nm, and calculated from the wavelength range of 550 nm to 1100 nm.
[0151] [Table 1]
[0152] Example 4 Synthesis of semiconductor nanoparticles In a reaction vessel, 0.4 mmol of silver acetate (AgOAc) and 0.4 mmol of indium acetate (In(OAc)3) were mixed with 8 mL of distilled and purified oleylamine (OLA), and dodecanethiol (1.25 mmol, 300 μL) was added to obtain liquid A. Separately, 0.8 mmol of 1,3-dimethylthiourea was dissolved in 2 mL of oleylamine to obtain liquid B. Liquid A was degassed and replaced with an argon atmosphere, and heated to 140°C. Liquid B was then added dropwise to liquid A over 30 minutes. The rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture (S / Ag ratio) was 0.067 / min. After the dropwise addition, the liquid temperature was kept at 140°C for 30 minutes. The mixture was then allowed to cool to room temperature, and coarse particles were removed by centrifugation, after which methanol was added to the supernatant to precipitate the semiconductor nanoparticles that would become the cores, which were then collected by centrifugation. The collected solid was dispersed in 2 mL of chloroform.
[0153] The XRD pattern of the obtained semiconductor nanoparticles was measured in the same manner as in Example 1. The measured XRD pattern is shown in Figure 11. Since no peak was observed around 48°, which is seen in orthorhombic crystals, it was confirmed that the crystal structure of the obtained semiconductor nanoparticles was substantially the same structure as that of tetragonal AgInS2.
[0154] The obtained semiconductor nanoparticles were observed using a transmission electron microscope in the same manner as in Example 1. The shape of the obtained particles is considered to be spherical or polygonal, similar to that in Examples. The average particle size and standard deviation of the semiconductor nanoparticles are shown in Table 2.
[0155] The amount of indium contained in the resulting semiconductor nanoparticles was determined by ICP emission spectrometry in the same manner as in Example 1, and the amount of indium as semiconductor nanoparticles was calculated to be 100 nmol.
[0156] Synthesis of core-shell semiconductor nanoparticles 0.1 mmol of gallium acetylacetonate (Ga(acac)3) and 0.1 mmol of 1,3-dimethylthiourea were measured and added to 8 mL of distilled and purified oleylamine, and then the chloroform dispersion of the semiconductor nanoparticles synthesized above was added as a dispersion of core particles in an amount equivalent to 30 nmol in terms of nanoparticle concentration. The resulting solution was degassed at about 60°C and replaced with an argon atmosphere, and then rapidly heated to 230°C (heating rate of about 60°C / min), and after 230°C, the temperature was further raised to 280°C at a rate of 2°C / min, and heat-treated at 280°C for 30 minutes. The solution was then allowed to cool to room temperature, methanol was added to precipitate the core-shell type semiconductor particles, and the resulting core-shell type semiconductor nanoparticles were dispersed in chloroform after washing.
[0157] Modification process A part of the obtained chloroform dispersion of the core-shell type semiconductor nanoparticles was used in the same manner as in Example 1 to obtain a dispersion of TOP-modified core-shell type semiconductor nanoparticles.
[0158] Measurement of absorption, emission spectra and quantum yield The results of measurement performed in the same manner as in Example 1 are shown in Table 2. The absorption spectrum is shown in FIG.
[0159] Example 5 Synthesis of semiconductor nanoparticles Core semiconductor nanoparticles were prepared in the same manner as in Example 4, except that the time for dropping the B solution was changed from 30 minutes to 60 minutes, and dispersed in 2 mL of chloroform.
[0160] The XRD pattern of the obtained semiconductor nanoparticles was measured in the same manner as in Example 1. The measured XRD pattern is shown in Figure 11. Since no peak was observed around 48°, which is seen in orthorhombic crystals, it was confirmed that the crystal structure of the obtained semiconductor nanoparticles was substantially the same structure as that of tetragonal AgInS2.
[0161] The obtained semiconductor nanoparticles were observed using a transmission electron microscope in the same manner as in Example 1. The shape of the obtained particles is considered to be spherical or polygonal, similar to that in Examples. The average particle size and standard deviation of the semiconductor nanoparticles are shown in Table 2.
[0162] Synthesis of core-shell semiconductor nanoparticles Using the obtained chloroform dispersion of semiconductor nanoparticles, core-shell type semiconductor nanoparticles were produced in the same manner as in Example 4.
[0163] Modification process A part of the obtained chloroform dispersion of the core-shell type semiconductor nanoparticles was used in the same manner as in Example 1 to obtain a dispersion of TOP-modified core-shell type semiconductor nanoparticles.
[0164] Measurement of absorption, emission spectra and quantum yield The results of measurement performed in the same manner as in Example 1 are shown in Table 1. The absorption spectrum is shown in FIG.
[0165] Example 6 Synthesis of semiconductor nanoparticles Core semiconductor nanoparticles were prepared in the same manner as in Example 4, except that the time for dropping the B solution was changed from 30 minutes to 15 minutes, and dispersed in 2 mL of chloroform.
[0166] The XRD pattern of the obtained semiconductor nanoparticles was measured in the same manner as in Example 1. The measured XRD pattern is shown in Figure 11. Since no peak was observed around 48°, which is seen in orthorhombic crystals, it was confirmed that the crystal structure of the obtained semiconductor nanoparticles was substantially the same structure as that of tetragonal AgInS2.
[0167] The obtained semiconductor nanoparticles were observed using a transmission electron microscope in the same manner as in Example 1. The shape of the obtained particles is considered to be spherical or polygonal, similar to that in Examples. The average particle size and standard deviation of the semiconductor nanoparticles are shown in Table 2.
[0168] Synthesis of core-shell semiconductor nanoparticles The obtained semiconductor nanoparticles were dispersed in chloroform and the same method as in Example 4 was used to prepare the semiconductor nanoparticles.
[0169] Modification process A part of the obtained chloroform dispersion of the core-shell type semiconductor nanoparticles was used in the same manner as in Example 1 to obtain a dispersion of TOP-modified core-shell type semiconductor nanoparticles.
[0170] Measurement of absorption, emission spectra and quantum yield The results of measurement performed in the same manner as in Example 1 are shown in Table 1. The absorption spectrum is shown in FIG.
[0171] [Table 2]
[0172] As shown in Table 2, in terms of the quantum yield of band edge emission of the core-shell semiconductor nanoparticles of Examples 4, 5, and 6, in which the increase rate of the S / Ag ratio (dropping time of liquid B) was changed, Example 4, in which the increase rate of the S / Ag ratio was 0.067 / min (dropping time of liquid B was 30 minutes), was the highest.
[0173] Example 7 Synthesis of semiconductor nanoparticles In a reaction vessel, 0.4 mmol of silver acetate (AgOAc), 0.24 mmol of indium acetate (In(OAc)3), and 0.36 mmol of gallium acetylacetonate (Ga(acac)3) were mixed with 8 mL of distilled and purified oleylamine (OLA), and dodecanethiol (3.47 mmol, 833 μL) was added to prepare liquid A. Separately, 1.2 mmol of 1,3-dimethylthiourea was dissolved in 2 mL of oleylamine to prepare liquid B. Liquid A was degassed and replaced with a nitrogen atmosphere, and heated to 180°C. Liquid B was then added dropwise to liquid A over 30 minutes. The rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture (S / Ag ratio) was 0.100 / min. After the completion of the dropwise addition, the liquid temperature was kept at 180°C for 30 minutes. The mixture was then cooled to room temperature, and coarse particles were removed by centrifugation. Methanol was added to the supernatant to precipitate the semiconductor nanoparticles that would become the cores, which were then collected by centrifugation. The collected solid was dispersed in 5 mL of hexane.
[0174] Synthesis of core-shell semiconductor nanoparticles 0.1 mmol of gallium acetylacetonate (Ga(acac)3), 0.15 mmol of 1,3-dimethylthiourea, and 36.5 mmol of tetradecylamine were measured out, and then the hexane dispersion of the semiconductor nanoparticles synthesized above was added as a dispersion of core particles in an amount equivalent to 30 nmol of nanoparticles. The reaction vessel was degassed to volatilize and remove hexane, and the atmosphere was replaced with nitrogen, and then the vessel was heated to 50°C to melt tetradecylamine. The temperature was then increased at 10°C / min until it reached 270°C, and heat-treated at 270°C for 60 minutes. The mixture was then allowed to cool to about 60°C, 3 mL of hexane was added, and coarse particles were removed by centrifugation. Methanol was then added to the supernatant to precipitate the core-shell semiconductor particles, which were then washed and dispersed in 3 mL of hexane.
[0175] Modification process The solvent of the obtained dispersion of core-shell semiconductor nanoparticles was replaced with chloroform, and a portion was taken and an equal amount of n-trioctylphosphine (TOP) was added and mixed, and the mixture was allowed to stand at room temperature for 24 hours to obtain a dispersion of TOP-modified core-shell semiconductor nanoparticles.
[0176] Measurement of absorption, emission spectra and quantum yield The absorption and emission spectra of the semiconductor nanoparticles, the core-shell type semiconductor nanoparticles, and the TOP-modified core-shell type semiconductor nanoparticles were measured. The results are shown in Figures 18 and 19. The absorption spectra were measured using an ultraviolet-visible-near infrared spectrophotometer (manufactured by Hitachi, product name U-2900) in the wavelength range of 350 nm to 750 nm. The emission spectra and emission quantum yields were measured and calculated using a quantum yield measurement system (manufactured by Otsuka Electronics, product name QE-2100) at room temperature (25°C) and an excitation wavelength of 450 nm in the wavelength range of 500 nm to 950 nm.
[0177] As shown in Figure 18, shoulders were observed near 515 nm and near 560 nm in the absorption spectrum of the core-shell semiconductor nanoparticles, suggesting that there is an exciton peak near 400 nm to 600 nm. In addition, as shown in Figure 19, band edge emission with a half width of about 28 nm was observed near 567 nm, the quantum yield of the band edge emission was 28.3%, and the purity of the band edge emission component was 55.9%. In addition, band edge emission with a half width of about 30 nm was observed near 569 nm in the emission spectrum of the TOP-modified core-shell semiconductor nanoparticles, the quantum yield of the band edge emission was 51.1%, and the purity of the band edge emission component was 71.0%.
[0178] The disclosures of Japanese Patent Application No. 2019-021769 (filed February 8, 2019) and Japanese Patent Application No. 2019-153620 (filed August 26, 2019) are incorporated herein by reference in their entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.
Claims
1. preparing a mixture including an Ag salt, a salt including at least one of In and Ga, and an organic solvent; heating the mixture to a temperature in the range of 120° C. to 300° C.; adding a source of S to the heated mixture so that the rate of increase in the ratio of the number of S atoms to the number of Ag atoms in the mixture is 10 / min or less; A method for producing semiconductor nanoparticles comprising the steps of:
2. Preparing a mixture containing an Ag salt, a Cu salt, a salt containing at least one of In and Ga, and an organic solvent; heating the mixture to a temperature in the range of 120° C. to 300° C.; adding a source of S to the heated mixture so that the rate of increase of the ratio of the number of S atoms to the total number of Ag and Cu atoms in the mixture is 10 / min or less; A method for producing semiconductor nanoparticles comprising the steps of:
3. 3. The method according to claim 2, wherein the ratio of the number of Cu atoms to the total number of Cu and Ag atoms contained in the mixture is 0.001 or more and 0.9 or less.
4. 4. The method according to claim 2, wherein a ratio of the total number of Cu and Ag atoms to the total number of In and Ga atoms contained in the mixture is 0.1 or more and 2 or less.
5. The method according to claim 1 , wherein the S source is added over a period of 15 minutes to 60 minutes.
6. The method according to any one of claims 1 to 5, wherein the S source is a solution of sulfur or a sulfur-containing compound.
7. The method according to any one of claims 1 to 6, further comprising heat treating the mixture after the addition of the S source is completed at a temperature in the range of 120°C to 300°C.
8. The method according to any one of claims 1 to 7, wherein an increasing rate of the ratio of the number of S atoms to the number of Ag atoms in the mixture is 0.025 / min or more and 0.19 / min or less.
9. The method of claim 1 , further comprising recovering the semiconductor nanoparticles after the addition of the S source, and dispersing the recovered semiconductor nanoparticles in a halogen-based solvent.
10. The method according to claim 1 , further comprising disposing a shell made of a semiconductor containing a Group 13 element and a Group 15 element on a surface of the semiconductor nanoparticle.
Citation Information
Patent Citations
Method for manufacturing quantum element
JP2002176166A
Phosphor and method for manufacturing the same
JP2007169605A
Semiconductor nanoparticle-containing film and semiconductor nanoparticle
JP2010013313A
Semiconductor nanoparticle and method for producing the same
JP2011178645A
Semiconductor nanoparticles, method of producing semiconductor nanoparticles, and light-emitting device
JP2018039971A